A 3D printed melt-compounded antibiotic loaded thermoplastic polyurethane heart valve ring design: an integrated framework of experimental material tests and numerical simulations. Issue 1 (11th February 2019) - Gasparotti, Emanuele; Vignali, Emanuele; Losi, Paola; Scatto, Marco; Fanni, Benigno Marco; Soldani, Giorgio; Landini, Luigi; Positano, Vincenzo; Celi, Simona
Abstract: Heart diseases are one of the commonest causes of death worldwide. These include valve pathologies such as valve stenosis, regurgitation, failure and similar, for which usually a valve substitution procedure is required. Different prosthesis alternatives (both biological and artificial) are nowadays available in the heart surgery panorama, but there are still issues and aspects to improve. The principal requirements for heart valve prostheses are an efficient fluid dynamic function and long-term durability without the need for anticoagulation therapy, coupled with the possibility of patient-specific customization. Given this scenario, the presented tasks might be fulfilled by the recent advances of additive manufacturing technology (AM), which offers versatility of shapes and materials to be printed. In this work, the full flexibility of AM technique has been exploited to demonstrate the feasibility of a custom drug-loaded polymeric heart valve ring for crimpable prostheses. Two different medical-grade polymeric filaments for AM have been extruded: an aromatic Polyester-Based Thermoplastic Polyurethane (TPU-E) and a Thermoplastic Silicone-Polycarbonate-urethane compound filament (TSPCU). Both materials find different applications in medical fields, thanks to their mechanical and biocompatibility features. A drug-loading procedure has been set to obtain an antibiotic-filled polymer material and the relative biocompatibility has been consequently investigated. Specimens have been printed with a Fused Deposition Method and uniaxial traction tests have been performed at different printing temperatures and infill orientation angles. To evaluate the damaging risk given by the HVR crimping process, a Finite Element (FE) simulation of the crimping load has been set. The TSPCU has appeared to be the best material to realize the prosthesis in terms of tensile stress values. The ultimate mechanical characteristics of TSPCU have resulted to be higher if compared with TPU-E, regardless of raster orientation angle and temperature. The qualitative characterization of the drug loading process of TSPCU has been successful: standard disc diffusion method has revealed a well-defined inhibition zone on the bacterial culture. The effectiveness of the antibiotic has been maintained even after the extrusion and the printing process. The simulated crimping procedure on the HVR has revealed that the maximum Von Mises stress value is below the ultimate stress taken from experimental tests. The reported results demonstrate the feasibility of a crimpable antibiotic loaded HVR realized through TSPCU 3D printing. Graphical Abstract: